From Assessment for Learning to Assessment for Expansion: Proposing a New Paradigm of Assessment as a Sociocultural Practice - Nishizuka, Kohei (Journal of Teaching and Learning, 2022)
Although the importance of formative assessment has been recognized worldwide, the theoretical foundation is insufficiently captured within a broader sociocultural context that promotes teachers and students building an assessment culture. This study proposes a theoretical framework that supports the claim that formative assessment aims to accelerate an agentic process of transforming and improving the teaching–learning activity systems rather than helping teachers mold students with traditional values and cultural discourses. The characteristics of formative assessment were organized for each of the learning metaphors: acquisition, participation, and expansion. In this paper, assessment for expansion is defined as a form of formative assessment to facilitate expansive learning toward a process of making teaching–learning better, of which the functional core is sociocultural feedback with reference to situational criteria. Next, the theoretical discussions demonstrate that assessment for expansion emerges from making a third space and forming a culturally fitted tool for realistic and sustainable practical judgements. These conditions, which work within a continuum of problematic, ends-in-view, and expanded contexts, recognize the impact of assessments in associating a single student’s voice with a school- and community-wide problem. In conclusion, the possibilities and challenges of assessment for expansion are discussed from theoretical and practical perspectives.